PENINGKATAN KUALITAS KETERAMPILAN MENGAJAR GURU DENGAN PENDEKAN STEM BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR NEGERI 1 NAPAL KELUMBAYAN - Efendi, Ujang; Sukamto, Ismu; Pangestu, Deviyanti; Loliyana, Loliyana (Universitas Sanata Dharma, 2024)
The huge potential of the Kelumbayan coastal area is a treasure trove of local wisdom that promises to improve the population's economy and can be used as a source of learning based on local wisdom, it should be an important part of the student learning process. STEM is an interdisciplinary approach to learning in which students use science, technology, engineering, and mathematics in real contexts that connect schools, the world of work, and the global world that aims to build the literacy of the younger generation in these fields. The application of STEM combined with local wisdom as a learning resource for students is a new support for innovative learning for educators and students in Kelumbayan. The service was carried out in the Kelumbayan sub-district by presenting representatives of educators spread across several schools in seven villages. The service is carried out by applying the pretest first and the posttest at the end of the service program. Elementary school teachers in Kelumbayan District together have an understanding of the STEM learning approach and other innovative learning models that teach students, besides the simulation of teaching practice using this approach has provided enlightenment for teachers in carrying out classroom learning.